Targeted detection of sequence variants in cell-free DNA from cerebrospinal fluid in pediatric central nervous system tumors - O’Halloran, Katrina; Crotty, Erin E.; Christodoulou, Eirini; Leary, Sarah E.; Miller, Alexandra; Paulson, Vera A.; Lockwood, Christina M.; Margol, Ashley S.; Biegel, Jaclyn A. (Frontiers in Oncology, 2025)
The emergence of liquid biopsy technologies holds great promise in the cancer setting, including in pediatric central nervous system (CNS) tumors. In contrast to broad lower-depth sequencing, commonly referred to as low pass whole genome sequencing (WGS), targeted platforms with a higher depth of coverage have also been established. Here, we review targeted liquid biopsy techniques with applicability to pediatric CNS tumors. These include polymerase chain reaction (PCR), both droplet digital PCR and reverse transcription-based PCR, Sanger sequencing, and next-generation sequencing approaches that incorporate amplicon- and hybrid capture-based methods. The goal of this paper is to facilitate an understanding of these targeted techniques and provide a context for clinical relevance within disease categories, as well as a discussion on optimizing real-world implementation for pediatric CNS tumors.